2021
DOI: 10.15252/msb.202110396
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2–host proteome interactions for antiviral drug discovery

Abstract: Treatment options for COVID-19, caused by SARS-CoV-2, remain limited. Understanding viral pathogenesis at the molecular level is critical to develop effective therapy. Some recent studies have explored SARS-CoV-2-host interactomes and provided great resources for understanding viral replication. However, host proteins that functionally associate with SARS-CoV-2 are localized in the corresponding subnetwork within the comprehensive human interactome. Therefore, constructing a downstream network including all po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 147 publications
(205 reference statements)
6
86
0
Order By: Relevance
“…In order to develop a high-confidence list of viral-host PPIs, we compared our BioID dataset to three previously published proximity-labeling datasets [ 14 , 15 , 22 ]. “High confidence interactions” were those that were identified in at least three studies and four datasets, with degree of connection ≤ 3 for at least four datasets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to develop a high-confidence list of viral-host PPIs, we compared our BioID dataset to three previously published proximity-labeling datasets [ 14 , 15 , 22 ]. “High confidence interactions” were those that were identified in at least three studies and four datasets, with degree of connection ≤ 3 for at least four datasets.…”
Section: Resultsmentioning
confidence: 99%
“…Datasets were obtained from three separate studies [ 14 , 15 , 22 ]. Interactions deemed significant by respective authors were compiled in one excel spreadsheet without filtering out preys identified across multiple baits.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, both NHERF1 and SNX27 also modulate TJ organization and barrier function, by associating with the TJ protein ZO-2 (SNX27) and regulating cytoskeletal organization and membrane trafficking [ 84 , 85 ]. Finally, proximity label mass spectrometry analysis identifies occludin as proximal to ACE2 (ACE2 BioGrid data, [ 86 ]). Together, these observations further reinforce the notion of a mechanistic link between TJ membrane and scaffolding proteins, ACE2 and SARS-CoV-2 entry.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previously conducted studies use standard sequence database searching to process AP-MS data [2, 7-10]. Most search engines require the user to explicitly specify potential protein modifications to be considered during searching.…”
Section: Introductionmentioning
confidence: 99%